Music Genre as a Predictor of Resource Utilization at Outdoor Music Concerts. Issue 3 (20th February 2017) - Westrol, Michael S.; Koneru, Susmith; McIntyre, Norah; Caruso, Andrew T.; Arshad, Faizan H.; Merlin, Mark A.
Abstract: Objectives: The aim of this study was to examine the various modern music genres and their effect on the utilization of medical resources with analysis and adjustment for potential confounders. Methods: A retrospective review of patient logs from an open-air, contemporary amphitheater over a period of 10 years was performed. Variables recorded by the medical personnel for each concert included the attendance, description of the weather, and a patient log in which nature and outcome were recorded. The primary outcomes were associations of genres with the medical usage rate (MUR). Secondary outcomes investigated were the association of confounders and the influences on the level of care provided, the transport rate, and the nature of medical complaint. Results: A total of 2, 399, 864 concert attendees, of which 4, 546 patients presented to venue Emergency Medical Services (EMS) during 403 concerts with an average of 11.4 patients (annual range 7.1-17.4) each concert. Of potential confounders, only the heat index ≥90°F (32.2°C) and whether the event was a festival were significant (P=.027 and .001, respectively). After adjustment, the genres with significantly increased MUR in decreasing order were: alternative rock, hip-hop/rap, modern rock, heavy metal/hard rock, and country music (P<.05). Medical complaints were significantly increased with alternative rock or when the heat index was ≥90°F (32.2°C; P<.001). Traumatic injuries were most significantly increased with alternative rock (P<.001). Alcohol or drug intoxication was significantly more common in hip-hop/rap (P<.001). Transport rates were highest with alcohol/drug intoxicated patients (P<.001), lowest with traumatic injuries (P=.004), and negatively affected by heat index ≥90°F (32.2°C; P=.008), alternative rock (P=.017), and country music (P=.033). Conclusion: Alternative rock, hip-hop/rap, modern rock, heavy metal/hard rock, and country music concerts had higher levels of medical resource utilization. High heat indices and music festivals also increase the MUR. This information can assist event planners with preparation and resource utilization. Future research should focus on prospective validation of the regression equation. Westrol MS, S Koneru, N McIntyre, Caruso AT, FH Arshad, MA Merlin .Music genre as a predictor of resource utilization at outdoor music concerts .Prehosp Disaster Med .2017 ;32 (3 ):289 –296 .